«SAVING» A TWO-STAGE LIVER RESECTION BY THE ALPPS TYPE - D. V. Sidorov; M. V. Lozhkin; L. O. Petrov; A. G. Isaeva (Исследования и практика в медицине)
A gold standard for the treatment of metastases of colorectal cancer in the liver is combined treatment with postoperative or perioperative chemotherapy. Despite the improvement of antitumor drugs, the main condition for the successful treatment of patients with metastatic colorectal cancer is the operation in a radical volume, implying a macroscopic and microscopic absence of a residual tumor. The main contraindications to anatomic resections of the liver include a marked decrease in liver function, insufficient volume of the remaining parenchyma of the liver, and for a long time, bilobar liver damage was considered, which excludes the possibility of simultaneous removal of all foci.The traditional variant of the surgical solution of the problem of bilobar metastatic liver injury is the implementation of two-stage anatomical resections. It has been proved that the reduction of liver and FLR functional reserves of less than 20% at normal and 40% in the case of compromised liver parenchyma, the implementation of surgical interventions is associated with a high risk of hepatic insufficiency. One of the promising ways to overcome this obstacle is to perform various modifications of ALPPS liver resections.In the present work, we present a clinical case of performing a two-stage liver resection according to the type of ALPPS in a patient with metastatic colorectal liver cancer who had previously undergone PVL with unrealized vicar hypertrophy. The described observation testifies to the justification of performing repeated liver resections in patients with metastatic colorectal cancer and demonstrates the possibilities of ALPPS technique.